Analyses of hospitalization in Alzheimer's disease and Parkinson's disease in a tertiary hospital - Chen, Sihui; Fu, Jiajia; Lai, Xiaohui; Huang, Yan; Bao, Ting; Chen, Xueping; Shang, Huifang (Frontiers in Public Health, 2023)
Background To characterize the pattern of hospitalization in patients with Alzheimer's disease (AD) or Parkinson's disease (PD), and compare the differences to see whether AD patients and PD patients have a different picture of hospitalization. Methods The clinical features of all consecutive patients from January 2017 to December 2020 were reviewed. We identified AD patients and PD patients from an electronic database in a tertiary medical center. Results The study group comprised 995 AD patients and 2,298 PD patients who were admitted to the hospital for the first time, and re-hospitalized 231 AD patients and 371 PD patients were also included. AD patients were older than PD patients when they were hospitalized (p < 0.001). AD patients had longer lengths of stay, higher re-hospitalization rates, and higher intrahospital mortality rates than PD patients during hospitalization even after adjusting age and gender. PD patients had higher levels of total cost than AD patients due to the cost of the deep brain stimulation (DBS) insertion. Hospitalizations for AD patients occurred most often in the department of geriatrics, while most PD patients were admitted to the department of neurology. Hospitalization due to the presence of comorbid conditions was much higher in AD patients, but a larger proportion of PD patients were hospitalized due to PD disease itself. Conclusions The present study found that AD patients and PD patients have a significantly different picture of hospitalization. It is important to implement different management for hospitalized AD and PD, and different emphasis should be given when establishing primary prevention strategies, informing care needs, and guiding healthcare resource planning.